Can augers be used to blend diets on the farm? - Johnston, S.L.; Hines, Robert H.; Traylor, S.L.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Growing/finishing gilts were fed two-, three-, four-, or five-phase diet regimens from 77 to 276 lb. The diets were mixed in either a conventional, horizontal ribbon mixer or a 9 ft auger. No interactions occurred among the mixer type and phase-feeding treatments. Pigs fed diets blended with the auger had similar ADG but slightly (4%) worse F/G compared to those fed diets mixed in the mixer. Finally, the three-phase regimen gave the lowest F/G and the lowest cost of gain.
Keywords: Swine; Phase-Feeding; Finishing; Mixing